The Effect of Brand Image and Perceived Quality on Purchase Intention with Brand Trust as Intervening Variable Studies on Marketplace Users - Sabilla Raihanah; Osly Usman; Rahmi (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to determine the effect of brand image on purchase intention, the effect of perceived quality on purchase intention, the effect of brand trust on purchase intention, the effect of brand image on brand trust, the effect of perceived quality on brand trust, the effect of brand image on purchase intention with brand trust as intervening variable, the effect of perceived quality on purchase intention with brand trust as intervening variable studies on marketplace users in Jakarta. The survey method with an instrument in the form of a questionnaire is a data collection method used by researchers using non-probability sampling techniques. The sample of this research is 222 respondents who have used Shopee and are citizens of Jakarta aged minimum 17 years. Data analysis used SPSS version 26 and SEM (Structural Equation Model) from AMOS version 26 software to process and analyze research data. The result of this study indicates: 1) brand image has a signigficant effect on purchase intention 2) perceived quality has a significant effect on purchase intention 3) Brand trust doesn’t have significant effect on purchase intenton 4) brand image has a significant effect on brand trust 5) perceived quality has a significant effect on brand trust 6) brand trust as intervening does not able to effect perceived quality to purchase intention 7) brand trust as intervening does not able to effect perceived quality to purchase intention.